Numerical analysis of fluid-added parameters for the torsional vibration of a Kaplan turbine model runner - Soltani Dehkharqani, Arash; Cervantes, Michel J; Aidanpää, Jan-Olov (Advances in mechanical engineering, 2017)
The impact of fluid on the runner of a hydraulic turbine is a recurrent problem. Fully coupled fluid–structure simulations are extremely time-consuming. Thus, an alternative method is required to estimate this interaction to perform a reliable rotor dynamic analysis. In this article, numerical estimations of the added inertia, damping, and stiffness for a Kaplan turbine model runner are presented using transient flow simulations. A single-degree-of-freedom model was assumed for the fluid–runner interaction, and the parameters were estimated by applying a harmonic disturbance to the angular velocity of the runner. The results demonstrate that the added inertia and damping are important, whereas the stiffness is negligible. The dimensionless added polar inertia is 23%–27% of the reference value ( ρ R 5 ) . Damping significantly contributes to the moment at low excitation frequencies, whereas the inertia becomes dominant at higher frequencies.